Aditivo alternativo reductor de gases contaminantes (co2, co, nox, so2), para calderas con combustión a diésel utilizados en la industria textil - Villegas Bosque, Jorge Sebastian (2017)
The objective of the research is to develop an alternative additive for boilers with diesel combustion as alternative for the textile industry to reduce the parameters in the gas pollutants produced by the boilers, which are used by the textile sector in the Pelileo, town Tungurahua, province began with the determination of the type of contamination through visits to the textile factory activity that allowed the lifting of the information needed for the research project. Subsequently identified the type of pollution produced by the boiler, applying the method of direct observation and the taking of data with all the information concerning the boiler, it was necessary to perform analysis of air to the boiler which was taken in the chimney by which emit the pollutant gas produced by the combustion it performs, it has a height of 12m and a diameter of 0.40m. To facilitate the study comparisons were made between the data got and the maximum permissible limits, which resulted in emissions being above the maximum permissible limits generating atmospheric pollution, with the need to remedy this problem I proposed the creation of an additive which would counteract the for this reason the researcher purposes, select the chemical compounds to be used to develop the additive which contains a solvent which is a viscous and colorless liquid with a mild odor and high solubility and a solvent catalyst commonly used to dilute paint. Created the additive with the required environmental characteristics, in turn determining the optimum dose to use the additive which is 0.05% of the total diesel fuel used by the boiler.